2019
DOI: 10.15446/esrj.v23n4.71706
|View full text |Cite
|
Sign up to set email alerts
|

Soil erosion risk zoning in the Ecuadorian coastal region using geo-technological tools

Abstract: The activation of erosive processes on the slopes of the drainage catchments in the Ecuadorian coastal region represents a serious environmental problem that results in a loss of soil resources with the consequent reduction in agricultural productivity, an increasing lack of areas with vegetation, and decreased water quality. These issues increase, among other things, the probability of flooding. The purpose of this research is to zone soil erosion risk in the Manabí province, which is located on the Ecuadoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 30 publications
1
1
0
1
Order By: Relevance
“…The results found are similar to those reported for some departments of the Andean area (Ramírez et al, 2009) (Castro et al, 2017) who primarily indicate erosivity classified as high and very high. These data are also consistent with the ranges indicated by Pacheco et al (2019) who reported erosivity values between 3162.12 and 12683.72 MJ.mm.ha -1 for an Ecuadorian tropical region and Liu et al (2020), who obtained average erosivity values for South America of 14378.64 MJ.mm.ha -1 between the years 1980-1999 and of 10273.67 MJ.mm.ha -1 , between 2000-2017. Figure 1 shows the distribution of the R factor in the area.…”
Section: Rainfall Erosivitysupporting
confidence: 91%
“…The results found are similar to those reported for some departments of the Andean area (Ramírez et al, 2009) (Castro et al, 2017) who primarily indicate erosivity classified as high and very high. These data are also consistent with the ranges indicated by Pacheco et al (2019) who reported erosivity values between 3162.12 and 12683.72 MJ.mm.ha -1 for an Ecuadorian tropical region and Liu et al (2020), who obtained average erosivity values for South America of 14378.64 MJ.mm.ha -1 between the years 1980-1999 and of 10273.67 MJ.mm.ha -1 , between 2000-2017. Figure 1 shows the distribution of the R factor in the area.…”
Section: Rainfall Erosivitysupporting
confidence: 91%
“…On the other hand, studies carried out in areas near this region by Ramírez et al (2009) and Castro et al (2017) indicate values of erosivity that are between the high and very high categories. Likewise, a study developed by Pacheco et al (2019) reports erosivity values framed between 3162.12 and 12683.72MJ.mm.ha -1 for an Ecuadorian tropical region, and more recently, Yue et al (2020) report values for the last two decades for South America up to 10273.67MJ.mm.ha -1 .…”
Section: Agroclimatic Effects On Erosion In Pineapplementioning
confidence: 98%
“…However, some investigations such as those carried out by (Ramírez et al, 2009) (Castro et al, 2017) in the departments of Caldas and Quindío, where the annual rainfall is between 1700 to 4000 mm, reporting erosivities classified as high and very high. On the other hand, a study carried out by Pacheco et al, (2019) for an Ecuadorian tropical region, indicated that the ranges of erosivity are between 3162.12 and 12683.72 MJ.mm.ha -1 yr -1 .…”
Section: Erosivity (R Factor)mentioning
confidence: 99%